Combined metabolomics and proteomics reveals hypoxia as a cause of lower productivity on scale‐up to a 5000‐liter CHO bioprocess. Issue 9 (29th June 2016) - Gao, Yuanwei; Ray, Somak; Dai, Shujia; Ivanov, Alexander R.; Abu‐Absi, Nicholas R.; Lewis, Amanda M.; Huang, Zhuangrong; Xing, Zizhuo; Borys, Michael C.; Li, Zheng Jian; Karger, Barry L.
Abstract: Large‐scale bioprocessing is key to the successful manufacturing of a biopharmaceutical. However, cell viability and productivity are often lower in the scale‐up from laboratory to production. In this study, we analyzed CHO cells, which showed lower percent viabilities and productivity in a 5‐KL production scale bioreactor compared to a 20‐L bench‐top scale under seemingly identical process parameters. An increase in copper concentration in the media from 0.02 µM to 0.4 µM led to a doubling of percent viability in the production scale albeit still at a lower level than the bench‐top scale. Combined metabolomics and proteomics revealed the increased copper reduced the presence of reactive oxygen species (ROS) in the 5‐KL scale process. The reduction in oxidative stress was supported by the increased level of glutathione peroxidase in the lower copper level condition. The excess ROS was shown to be due to hypoxia (intermittent), as evidenced by the reduction in fibronectin with increased copper. The 20‐L scale showed much less hypoxia and thus less excess ROS generation, resulting in little to no impact to productivity with the increased copper in the media. The study illustrates the power of 'Omics in aiding in the understanding of biological processes in biopharmaceutical production. Abstract : For biopharmaceutical industrial scale production, productivity is often reduced compared to laboratory scale using seemingly identical parameters. The authors found that in a 5‐kL reactor, an increase in copper concentration increased titer, but still below a 20‐L scale, the latter with only minor change from copper increase. Combined metabolomics and proteomics revealed that the 5‐kL was under increased oxidative stress compared to the 20‐L scale and that this stress was due to intermittent hypoxia in the industrial scale resulting in lower titer.